The Importance Performance Analysis of Taiwan Tourism Mobile Marketing - Chang, Peggy (Journal of Tourism Management Research, 2017)
The growing power of the Internet, mobile technology and smart phones has offered new marketing services in tourism industry. Mobile marketing services becomes the most important factor in creating of marketing strategies. This study consider tourism mobile marketing application types in six major aspects: transportation, accommodation, food, tour, community and other, combined with Technology Acceptance Model of usefulness, ease of use and interesting; Analyze of the satisfaction and importance of users by Importance Performance Analysis (IPA). The results showed: user perception of each application in tourism mobile marketing, important susceptibility is higher than satisfaction; ease of use is the most important; real time and correct information are important, but not in good satisfactory, should be in the most need to improve.